Próba Twardości Rockwella jako Problem Teorii Plastyczności - Tien, Dao-Duy (Engineering Transactions, 1973)
The paper is aimed at determination of minimal dimensions of a specimen subjected to the Rockwell hardness test. The problem is formulated within the framework of the theory of flow of rigid-perfectly plastic incompressible materials obeying the flow rule associated with the Tresca yield condition, and under the assumption of absence of friction between the cone and the specimen tested. Theoretical results are verified by means of experiments.